(untitled) (Victoria Journal of Management, 2025)
This systematic review analyzes 94 articles published from 2020 to 2025 on sustainable behaviors and green consumption among consumers. Growing concerns about climate change and ethical consumption have heightened interest in research on green consumer behavior. Using the Scopus database, the study highlights key aspects of the literature, including the most cited articles, contributions by country, frequently used keywords, and leading journals based on citation count. The study highlights that research on sustainability primarily centers on China, the UK, India, and the US, reflecting significant institutional and academic interest. Most studies employed quantitative methods, particularly Structural Equation Modeling (SEM), to examine the links between environmental concern, consumer attitudes, and sustainable behaviors. Key themes identified include green products, pro-environmental behavior, and sustainability values. Additionally, a thematic analysis reveals recurring patterns and conceptual themes across the reviewed literature. This offers deeper insight into the psychological, social, and technological factors influencing sustainable consumer practices. Despite the growing body of research, significant gaps remain. Underrepresentation of developing countries persists, and the attitude–behavior gap is present in most settings. The review helps by mapping the landscape of consumer research for sustainability and urging future research to be more comprehensive, interdisciplinary, and action-focused. The conclusions could guide policymakers, businesses, and researchers who aim to promote sustainable consumption both locally and globally.